Effect of cyclosporine therapy in transplanted patients-diagnostic values of tubular markers - Todor Gruev; Lidija Petrushevska-Tozi; Koco Chakalarovski; Ninonslav Ivanovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2003)
The introduction of cyclosporine A (CsA) into the clinical practice has resulted in a major improvement in the short-term outcomes of solid organ transplantation and treatment of autoimune diseases. Chronic ScA nephrotoxicity has been described in kidneys of recepients of renal and other organ allografts. However, the exact mechanism underlying the development of fibrosis in chronic CsA nephrotoxicity has remained poorly understood. Evaluation with the validation data set showed that noninvasive urine protein differentiation might be a useful diagnostic strategy in nephrology. Over the past decade numerous studies in patients after transplantation have demonstrated that renal tubular cell injury after a toxic insult, results in sloughing of tubular debris and cell into the tubular lumen with eventual obstruction of tubular flow, increased intratubular pressure and backleak of glomerular filtrate out of the tubule. Urinary enzymes and low molecular proteins have been recommended as useful markers for the detection of changes in the kidney tissue in cases after renal transplantation. The aim of our study was to monitor the concentration and eventual nephrotoxic effect of Cyclosporine A using the concentration of low molecular proteins α-1-microglobulin and β−2-microglobulin, serum Cystatin C, as well as the concentration of isoform of GST-α and π.